Accident and emergency services for children within Trent region. Issue 3 (1st May 2001) - Playfor, S
Abstract : Objectives —To investigate the provision of accident and emergency (A&E) services for children within Trent region, and to compare these with published recommendations. Methods —A postal questionnaire was sent to all A&E and minor injury units within Trent region providing services for children. Findings were compared with published recommendations including those of the Multidisciplinary Working Party into Accident and Emergency Services for Children. Results —Thirty six units provided A&E services for children within Trent: 17 mixed units, 17 minor injury units and two children's units. Within mixed A&E units complete audio-visual separation from adult patients was provided by six units (35%), inpatient paediatric facilities were available at 11 units (65%) and a minimum of one registered children's nurse was always on duty in three units (18%). Conclusions —Few A&E units within Trent region currently meet the recommendations of the Multidisciplinary Working Party. The most common shortfall identified was in the provision of registered children's nurses.